2016
DOI: 10.1099/ijsem.0.001302
|View full text |Cite
|
Sign up to set email alerts
|

Candida vulturna pro tempore sp. nov., a dimorphic yeast species related to the Candida haemulonis species complex isolated from flowers and clinical sample

Abstract: In a taxonomic study of yeasts isolated from flowers in Cagayan de Oro, Mindenao Island, The Philippines, strains were identified as representing Kabatiella microsticta, Metschnikowia koreensis and a hitherto undescribed dimorphic species. Sequences of the D1/D2 domains of the LSU 26S rRNA genes, the internal transcribed spacer (ITS) regions and the SSU 18S rRNA genes were identical in the strains of the last-named group and differed from the corresponding sequences of the type strain of the closest related sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 39 publications
3
72
0
Order By: Relevance
“…vulnera. 33 C. auris is an ovoid to elongate budding yeast, which seldom forms rudimentary pseudohyphae 6,27,34 and typically appears as pink, but sometimes white or red, colonies on CHROMagar Candida or CAN2 chromogenic medium. 31,35 This organism has a high tolerance for salinity and heat.…”
Section: Biology and Morphologymentioning
confidence: 99%
“…vulnera. 33 C. auris is an ovoid to elongate budding yeast, which seldom forms rudimentary pseudohyphae 6,27,34 and typically appears as pink, but sometimes white or red, colonies on CHROMagar Candida or CAN2 chromogenic medium. 31,35 This organism has a high tolerance for salinity and heat.…”
Section: Biology and Morphologymentioning
confidence: 99%
“…Although the phylogenetic analyses performed suggested that the new species described here belong to the family Metschnikowiaceae and are closely related to Clavispora, studied isolates cannot be unequivocally assigned to this genus. Additionally, previous studies have demonstrated that C. auris and C. haemulonis are distant from Clavispora lusitaniae and do not constitute a monophyletic group [20,42]. Therefore, we propose to refer to these novel species as Candida metrosideri pro tempore sp.…”
Section: Plos Onementioning
confidence: 94%
“…nov. The term 'pro tempore' was proposed to indicate lineages that are temporary generic assignments in absence of further taxonomic evidence [20,43].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…1 Its closest phylogenetic relationship is with Candida haemulonii. [1][2][3][4][5] Whole genome sequencing (WGS) data indicate nearsimultaneous emergence of C. auris and spread of independent clones, rather than global transmission of one clone. 6 Four main geographic-specific clades have been described -South Asia, South Africa, South America and East Asia 6each separated by many tens of thousands of single nucleotide polymorphisms.…”
Section: Introductionmentioning
confidence: 99%